Enzymatic debridement in scalds is not as effective as in flame burns regarding additional eschar excision: a retrospective matched-control study - Tapking, Christian; Siegwart, Laura; Jost, Y.; Hundeshagen, Gabriel; Kotsougiani-Fischer, Dimitra; Gazyakan, Emre; Bliesener, Björn; Kneser, Ulrich; Fischer, Sebastian (Burns, 2022)
Objective - Enzymatic debridement of burn eschar became an accepted and widely used technique for burn wound treatment over the last years. However, this practice is not exempt from failure and recent experimental studies indicate that it may not be as efficient in scalds as in flame burns. - Methods - Patients that were admitted to the burn intensive care unit between June 2017 and February 2021 and received enzymatic debridement within the first 72 h after scald and flame burn were included. Patients with scald burns were matched regarding age, sex and per cent total body surface area (%TBSA) burned in a 1:2 ratio with patients presenting with flame burns. - Results - Eighteen patients with scald burns were matched with 36 with flame burns. After matching, both groups were similar in terms of age (flame burns 44.5 ± 21.1 years vs. scald 41.8 ± 22.6 years, p = 0.666), and %TBSA burned (11.0 ± 8.2% vs. 10.6 ± 9.6%, p = 0.851). Patients with scald burns significantly more often underwent further surgical eschar excision compared to controls (scald 16 (88.9%) vs. flame 19 (52.8%), p = 0.016). Length of stay per %TBSA was significantly longer in scald burns (scald 7.8 ± 9.2 days vs. flame 3.7 ± 3.8, p = 0.013). - Conclusion - This study indicates that enzymatic debridement may not be as effective in scalds as in flame burns. It was shown that patients with scalds and subsequent enzymatic debridement more frequently underwent additional surgical intervention and that the size of the transplanted area was larger compared to control. Moreover, those patients had a longer length of stay at the hospital per %TBSA burned.
Gesehen am 11.10.2022